How effective are automatic fiscal stabilisers in the OECD countries? - Maravalle, Alessandro (OECD Economics Department Working Papers, 2020)
This paper proposes an approach to assess the extent of automatic fiscal stabilisation of aggregate household disposable income after a specific shock. The approach is based on the national account identity of household disposable income and elements of the OECD methodology to cyclically adjust budget balances. In a stylised scenario assuming a decline in household market income, automatic stabilisers in 23 OECD countries are found to offset on average around 60% of the shock on impact. Direct taxes provide larger stabilisation than social benefits and social security contributions. There are important differences in the effectiveness of automatic stabilisers across the OECD countries. They mainly reflect non-linear interactions among the size of a specific automatic stabiliser, the elasticity of the automatic stabiliser with respect to a relevant economic variable and the specific shock scenario analysed